Examining the knowledge and attitude of nursing and midwifery students of medical sciences universities of Mazandaran province in the field of pain management and related factors in 2023 - Farahnaz Heshmat; Negar Asgharipour; Ashraf Beirami; Seydeh Zeynab Hoseinnezhad; Maryam Naji Abhary (Wolters Kluwer Medknow Publications, 2024)
Considering the importance of pain management and the complications of non-management by nurses, the present study was carried out with the aim of determining the knowledge and attitude of nursing and midwifery students of medical sciences universities of Mazandaran province in the field of pain management and related factors in 2022. The current research is a cross-sectional study (descriptive and analytical) that was conducted at Universities of Medical Sciences of Mazandaran Province. The sample size was calculated to be 207 people who were selected from nursing and midwifery students of the 5th to 8th semesters who were eligible to enter the study by systematic random sampling. The data collection tools were: a demographic profile questionnaire, a Nurses' Attitude Survey (NAS), a Nurses' Knowledge Assessment Questionnaire in the field of pain management, Pain Management Principles Assessment Test (PMPAT). Experiment and data analysis were conducted with SPSS software version 26. The average age of the students was 21.61. The gender of most people (207 people) was female. The average score of knowledge about pain management was 41.53 ± 10.30 and the average score of attitude toward pain management was 65.24 ± 5.26 (on average). The results of the Mann-Whitney test indicated that there was a statistically significant difference between the average knowledge and attitude toward pain management according to gender (female), educational background, university semester, having a student work experience (P < 0.05). Also, Spearman's test showed that there is a positive and significant correlation between students' knowledge and attitude (R = 0.324), which was statistically significant (P < 0.05). The results of this study indicate that the amount of knowledge and attitude toward pain management in the studied nursing and midwifery students is average. In examining the factors related to pain management of patients, things like gender, education history, university semester, having a student work history are related to the level of knowledge and attitude. In this way, it seems necessary to carry out educational interventions in order to increase the knowledge and improve the attitude of students toward pain management.